Upaya Meningkatkan Keterampilan Menulis Narasi Menggunakan Metode Contextual Teaching and Learning Pembelajaran Bahasa Indonesia di Mi Rahmatullah Kota Jambi - Aura Ariza Salwa; Yudha Rello Pambudi (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
This study aims to improve the narrative writing skills of third grade students of MI Rahmatullah Jambi City through the application of the Contextual Teaching and Learning (CTL) method. This research is a Classroom Action Research (PTK) conducted in two cycles, each consisting of two meetings. Each cycle includes the stages of planning, implementation, observation, and reflection. Data were collected through observation of educators' and learners' activities, as well as assessment of students' narrative writing results. The results showed a significant increase in learning activities and students' narrative writing skills. The average score of teacher activity increased from 42.9 in Cycle I Meeting I to 96.5 in Cycle II Meeting II. Learners' activities also increased from a score of 54.5 to 80.4 at the end of the cycle. In addition, the average score of students' narrative writing skills increased from 44.9 at the pre-cycle stage to 89.5 at the end of Cycle II. These findings prove that the CTL method is effective in creating active, meaningful learning and improving narrative writing skills. Thus, CTL method is recommended as an innovative learning strategy in Indonesian language learning.